Implementation of the ERAS protocol in gynecology and oncogynecology - evaluation of a pilot study - Brtnický, Tomáš; Malecová, Markéta; Koliba, Peter; Hubka, Petr; Sládková, Petra; Hodyc, Daniel; Škodová, Magdaléna; Zikán, Michal (Ceska gynekologie, 2023)
OBJECTIVE: To describe the implementation process and evaluate the success of compliance with the recommended ERAS protocol in the Czech healthcare system. METHODS: The study included 163 patients from March to September 2022, a total of 7 months. Patients were divided into three groups according to the type of surgery. Clinical protocol: Oncogynecology, hysterectomy and laparoscopy. The implementation was realized in three phases (preparation, implementation of the protocol itself and evaluation). RESULTS AND CONCLUSIONS: The cumulative adherence rate was 90% or more in all three groups. Based on the pilot results at our department, we evaluated the ERAS concept as a well-implemented tool for gynaecological departments in the Czech healthcare system.
Keywords: Postoperative Complications; Guideline Adherence; pilotní projekty; Clinical Protocols; laparoskopie; pooperační komplikace; Gynecology; adherence; lidé; ženské pohlaví; dodržování směrnic; Humans; implementation; Laparoscopy; Pilot Projects; klinické protokoly; gynekologie; Female; ERAS